Coronary Microvascular Dysfunction Correlates With the New Onset of Cardiac Allograft Vasculopathy in Heart Transplant Patients With Normal Coronary Angiography. Issue 5 (12th March 2015) - Tona, F.; Osto, E.; Famoso, G.; Previato, M.; Fedrigo, M.; Vecchiati, A.; Perazzolo Marra, M.; Tellatin, S.; Bellu, R.; Tarantini, G.; Feltrin, G.; Angelini, A.; et al.
Abstract: Coronary microvascular dysfunction is emerging as a strong predictor of outcome in heart transplantation (HT). We assessed the validity of microvascular dysfunction, defined by means of a reduced coronary flow reserve (CFR), as a factor associated with new onset epicardial cardiac allograft vasculopathy (CAV) or death. We studied 105 patients at 4 ± 1 years post‐HT with a normal coronary angiography (CA). New onset CAV was assessed by CA. CFR was assessed in the left anterior descending (LAD) coronary artery by transthoracic Doppler echocardiography and calculated as the ratio of hyperaemic to basal blood flow velocity. A CFR ≤ 2.5 was considered abnormal. Epicardial CAV onset or death was assessed during a follow‐up of 10 years. New onset CAV was diagnosed in 30 patients (28.6%) (Group A), and the CA was normal in the remaining 75 patients (71.4%) (Group B). Group A had reduced CFR compared with group B (2.4 ± 0.6 vs. 3.2 ± 0.7, p < 0.0001). A CFR ≤ 2.5 was independently associated with a higher probability of new onset CAV (p < 0.0001) and a higher probability of death, regardless of CAV onset (p < 0.01). Microvascular dysfunction is independently associated with the onset of epicardial CAV, and associated with a higher risk of death, regardless of CAV onset. Abstract : This study shows that coronary microvascular dysfunction, defined by means of a reduced coronary flow reserve, is independently associated with the new onset of epicardial cardiac allograft vasculopathy.